Analisis Skala Ekonomi pada Industri Pengolahan Tahu di Kecamatan Gadingrejo Kabupaten Pringsewu - Mutiara Surya Indah; Emi Maimunah (Departement of Mathematics Education, 2023)
This study aims to analyze the effect of production value on business capital, wages, technology, and economies of scale in Gadingrejo District. This study uses primary data with a total of 35 respondents to the tofu industry in Gadingrejo District using a multiple linear regression model. The dependent variable used is production value and the independent variables include capital, wages and technology. The results showed that capital, wages, and technology had a positive and significant effect on the production value of tofu companies in Gadingrejo District, Pringsewu Regency.